"Zusammenspiel zwischen Moskau und Prag gegen die Sudetendeutschen dokumentarisch erwiesen". Serie von 2 Fotos
"Zusammenspiel zwischen Moskau und Prag gegen die Sudetendeutschen dokumentarisch erwiesen". Serie von 2 Fotos.